Purification, crystallization and preliminary X-ray diffraction analysis of the Hsp40 protein CPIP1 from Nicotiana tabacum - Grießl, Martin; Jungkunz, Isabel; Sonnewald, Uwe; Muller, Yves (Acta Crystallographica Section F: Structural Biology and Crystallization Communications, 2012)
Chaperones promote many different molecular processes, including the folding, targeting and degradation of proteins. The best-studied chaperone system consists of the Hsp70s and their co-chaperones the Hsp40s. Chaperone function can be hijacked by viruses in plants. Potato virus Y interacts via its coat protein with an Hsp40 from Nicotiana tabacum, referred to as NtCPIP1, in order similar to to regulate replication. To understand the molecular determinants of this similar to mechanism, different variants of NtCPIP1 were expressed, purified and crystallized. While crystals of wild-type NtCPIP1 diffracted to 8.0 angstrom resolution, the deletion mutant NtCPIP1-(1:127) crystallized in space group P21212 and diffracted to 2.4 angstrom resolution.
Keywords: plant heat-shock protein 40; viral infections; potyviruses

Structural insight into the giant Ca²?-binding adhesin SiiE: implications for the adhesion of Salmonella enterica to polarized epithelial cells - Grießl, Martin; Schmid, Benedikt; Kaßler, Kristin; Braunsmann, Christoph; Ritter, Regina; Barlag, Britta; Stierhof, York-Dieter; Sturm, Karina U.; Danzer, Claudia Agnes; Wagner, Carolin; Schaeffer, Tilman E.; Sticht, Heinrich; et al. (Structure, 2013)
SiiE from Salmonella enterica is a giant 5,559-residue-long nonfimbrial adhesin that is secreted by a type 1 secretion system (T1SS) and initiates bacterial adhesion to polarized host cells. Structural insight has been gained into the 53 bacterial Ig-like (BIg) domains of SiiE, which account for 94% of the entire SiiE sequence. The crystal structure of a fragment comprising BIg domains 50 to 52 of SiiE reveals the BIg domain architecture and highlights two types of SiiE-specific Ca²?-binding sites. Sequence homology considerations suggest that full-length SiiE interacts with more than 100 Ca²? ions. Molecular dynamics simulations and single-molecule imaging indicate that Ca²? binding confers SiiE with a rigid 200 nm rod-like habitus that is required to reach out beyond the Salmonella lipopolysaccharide layer and to promote adhesion to host cells. The crystal structure suggests plausible routes for the establishment of the initial contact between Salmonella and host cells.
EVALuna2:7643